Double dividend of climate protection and the role of international policy coordination in the EU: an applied general equilibrium analysis with the GEM-E3 model - Klaus Conrad; Tobias F. N. Schmidt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1997)
While there is some hope that the ongoing climate change negotiations will soon come up with concrete, time scheduled and binding emission reduction commitments, the question of how to achieve these targets is still unsolved. The objective of this paper is to analyse alternative settings of an environmental tax reform and its economic and environmental impacts on the EU. The methodological framework used is based on a multi-country and multi-sectoral computable general equilibrium model for eleven EU-member states. The emphasis of the analysis lies on the institutional setting of a carbon dioxide reduction policy and on the specification of the labour market. The institutional settings analysed are related to the degree of environmental policy coordination. As standard neo-classics neglegt the problem of unvoluntary unemployment, we relax this restriction in the second part of the analysis in order to test alternative (more rigid) labour market specifications. The major findings of the paper can be summarized as follows: 1) There is some potential for a double dividend in the EU. 2) Coordination beats not always unilateral actions. 3) Labour market rigidities play a crucial role to both, the double dividend and the coordination issue.
Keywords: 330; Klimaschutz; Ökosteuer; Steuerreform; Internationale wirtschaftspolitische Koordination; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Kohlendioxid; Allgemeines Gleichgewicht; Arbeitsmarktflexibilisierung; EU-Staaten